Efeitos dos herbicidas clomazone e ametrina em parâmetros funcionais da espécie de peixe neotropical Prochilodus lineatus - Pereira, Lindalva (Universidade Federal de São Carlos, 2012)
The use of biomarkers can provide a great help in the evaluation of the damages caused by pesticides in aquatic organisms. The present study aimed to verify the toxicity of clomazone and ametryn for a tropical freshwater fish Prochilodus lineatus by using different parameters in fish exposed for 96h to clomazone (1, 5 and 10 mg.L-1) and to ametryn, as the commercial product GesapaxR500 or in its pure form, in the concentrations 2.5 and 5.0 mg.L-1, or only to water (CTR). The parameters used were: hematological; metabolic (concentration of glucose); osmoionic (osmolarity and plasmatic Cl-, Na+ e K+); biochemical and genotoxic (DNA damage). Clomazone caused hematological disturbances in P. lineatus as noted in the lowervalues of hematocrit (Hct) in 10 mg.L-1; hemoglobin (Hb), mean corpuscular hemoglobin (HCM) and mean corpuscular hemoglobin concentration (CHCM) in 5 and 10 mg.L-1, which, in general, may indicate anemia. The number of erythrocytes (RBC) presented increased values in the lowerconcentration tested for clomazone, which probable is related to the stress response, with the releasing of immature erythrocytes in the blood stream. Clomazone also activated the detoxification and antioxidant pathways of the tested animals, as shown by the increased activity of the hepatic biotransformation enzyme glutathione-S-transferase (GST) and the antioxidant enzyme catalase (CAT) in 5 and 10 mg.L-1. The reduced activity of glutathione peroxidase (GPx) observed in 5 and 10 mg.L-1 indicated efficient performance of CAT removing the H2O2, or even a competition with GST for the substratereduced glutathione (GSH). The activity of brain acetylcholinesterase (AChE) in P. lineatus was inhibited in the concentrations of 5 and 10 mg.L-1 of clomazone, showing that this herbicide has an anticholinesterasic effect on the studied fish species. Fish exposed to ametrynshowed hematological disturbances such as lower values of Hct in 2.5 and 5.0 mg.L-1 and of RBC in the concentration of 5.0 mg.L-1. The reduction of plasmatic K+ in the concentration of 2.5 mg.L-1, and the hematological alterations mentioned above, may indicate a rupture of the erythrocytes. Fish exposed both to pure ametrynand the formulated product, showed higher values of glucose as a stress response, in both concentrations tested. The two products also caused inhibition of the gill activity of Na+/K+ATPase in 5.0 mg.L-1. The concentration of 5.0 mg.L-1 caused significant decrease in the malondialdehyde (MDA) levels, leading to the conclusion that ametrynor its formulated product do not generate lipidic peroxidation. DNA damages in the erythrocytes of P. lineatus were x observed in the concentration of 5.0 mg.L-1 of ametryn and GesapaxR 500, showing the genotoxicity of ametryn, probably because it binds directly to the genetic material of the fish. The results presented here allow concluding that the pesticides ametryn and clomazone interfere in the functional parameters of P. lineatus and can compromise the health of these animals
Effects of the herbicides clomazone and ametryn on functional parameters of the neotropical species of fish Prochilodus lineatus
Keywords: Peixe; Acetilcolinesterase; Antioxidantes; Biotransformação; Hematologia; Herbicidas; Danos no DNA; Acetilcholinesterase; Antioxidants; Biotransformation; DNA damages; Pesticides; Hematology; Fish; CIENCIAS BIOLOGICAS::ECOLOGIA